The Association of Surgeons in Training Conference: #ASiT2015 Glasgow. (November 2015) - Gokani, V.J.; Beamish, A.J.; Sinclair, P.; Robson, A.; Harries, R.L.; ,
Abstract: The Association of Surgeons in Training (ASiT) is a professional body and registered charity working to promote excellence in surgical training for the benefit of junior doctors and patients alike. ASiT is in-dependent of the National Health Service (NHS), Surgical Royal Colleges, and specialty associations and represents trainees in all ten surgical specialties. ASiT was delighted to welcome a number of distinguished guests and speakers to Glasgow for #ASiT2015. The theme of 'The Future of Surgery' delved into challenges surgical training faces, exciting developments into using technology to help patients, a glance at the past with the development of the Glasgow Coma Score and whether mortality truly is the future of measured outcomes. More than £3500 of prizes was awarded by the incoming President, Miss. Rhiannon Harries to the highest scoring papers presented selected from over 1000 abstracts submitted.